(untitled) (Altre Modernità, 2014)
The purpose of this paper is to investigate, through the analysis of the writings of three German Jewish authors of second generation – Lea Fleischmann, Esther Dischereit and Barbara Honigmann – their different responses to the complex post-war situation of Jews in both West- and East-Germany. Despite the different origins and experiences of their parents under Nazism, all three make in their youth the painful experience of a Judaism lived mainly as absence, as silence about the past and as lack of Jewish tradition and religion. Trying to achieve their own identity, Fleischmann and Dischereit seek a possible integration in post-war West-Germany in the political commitment of the 70s, but must then recognize that anti-Semitism is still widespread in that country. This discovery compels Fleischmann to leave Germany and seek in Israel and eventually in the religion of her fathers a Jewish identity. Esther Dischereit decides on the contrary to perform in Germany her "exercises to be Jewish", assuming the role of critical conscience of German society. Different is the situation of Barbara Honigmann, born and raised in East-Germany, who reacts to the dominant materialism in that state with a need for spirituality that will take her to seek in religion – lived outside of Germany and so far from "negative symbiosis" between Jews and Germans, but also far from Israel - her own diasporic identity. Despite the three different outcomes resulting from the search for Jewish identity in post-war Germany, for all three authors writing plays a crucial function as memory and critical conscience and since this writing is a German one, it imposes eventually a tight and thorough confrontation with German culture.